Analysis of pulse transformer voltage ripple of invert type of modular structure - Кадацкий, Анатолий Федорович; Русу, Александр Петрович; Ерыкалина, Татьяна Николаевна; Криль, Александр Сергеевич (Technology audit and production reserves, 2015)
The mathematical models of voltage ripple in input and output circuits of pulse converters of DC modular structure with power channels of the inverting type are obtained and analyzed. The mathematical model is focused on the power of channels in the boundary mode operation that can reduce energy loss in the transformation. The mathematical model is generalized to the single-phase and multiphase transformation principles, auto-transformer and transformer connection of storage chokes of power channels. The methods and algorithms for calculating the voltage and current ripple in the input and output circuits of these converters are presented. The simulation results of the electrical processes in input and output converters with autotransformer turning of the choke are presented. It was established that the principle of multi-phase transformation reduces the magnitude of both fluctuations in the input and output circuits. This allows developing the converters with improved mass-dimensional and cost indicators.